Pengembangan Aplikasi Pemanfaatan Barang Milik Negara Berbasis Website Menggunakan Metode Waterfall - Nuril Qomaryah; Verdi Yasin; Anton Zulkarnain Sianipar (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2025)
Good management of State Property (BMN) is expected to be owned by every government agency, one of which is in the activity of borrowing goods. However, in the process, several obstacles were found, such as errors in recording goods due to manual processes, difficulties in searching for data, the length of time required to provide reports, frequent stock shortages, and difficulties in data processing. To overcome these problems, a BMN utilization information system has been built. Data was collected through interviews, observations, and literature studies. System development was carried out using the SDLC Waterfall method which consists of five stages, namely needs analysis, design, implementation, testing, and maintenance. System design was carried out using UML diagrams, such as use cases, activity diagrams, class diagrams, and mock-ups. Implementation was carried out using the PHP programming language with the Laravel framework and MySQL database. Testing was carried out using the black-box method and System Usability Scale with a test result score of 89.8 which means the application is suitable for use. A website-based BMN utilization application with the waterfall method and Laravel framework was produced from this study. From the research that has been conducted, it is concluded that the application that has been created is able to make it easier for agencies to manage BMN and is more optimal, especially borrowing activities and requests for inventory of goods become more effective and efficient.